2020
DOI: 10.1159/000511349
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Based Psychosocial Interventions for People with Borderline Personality Disorder: A Scoping Review of the Literature

Abstract: Evidence-based psychosocial interventions for borderline personality disorder (BPD) still face multiple challenges regarding treatment accessibility, adherence, duration, and economic costs. Over the last decade, technology has addressed these concerns from different disciplines. The current scoping review aimed to delineate novel and ongoing clinical research on technology-based psychosocial interventions for patients with BPD. Online databases (PubMed, Cochrane Library, EMBASE, Web of Science, PsycInfo, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…This study provides evidence that DBT delivered via email can be effective in reducing the severity of symptoms associated with borderline personality disorder. These findings concurrently add to literature on the efficacy of internet-based interventions for DBT, with more work needing to be done [ 23 ]. This innovative modality has the potential to increase the accessibility of mental health services for a large group of individuals who could benefit from these resources.…”
Section: Discussionmentioning
confidence: 62%
“…This study provides evidence that DBT delivered via email can be effective in reducing the severity of symptoms associated with borderline personality disorder. These findings concurrently add to literature on the efficacy of internet-based interventions for DBT, with more work needing to be done [ 23 ]. This innovative modality has the potential to increase the accessibility of mental health services for a large group of individuals who could benefit from these resources.…”
Section: Discussionmentioning
confidence: 62%
“…Mobile solutions are also available for anxiety and depressive disorders [23]. A scoping review of technology-based psychosocial interventions for patients with BDP was undertaken in 2020 and identified potential software packages in terms of their research development level, with limited evidence provided about the effectiveness of these interventions [24]. Computer-driven technologies are evolving fast and there is a need to explore the effectiveness of these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses showed the efficacy of IMIs for various mental disorders (e.g., [ 8 10 ]), as yet mostly based on Internet-based interventions, while evidence for MHAs is less established [ 11 ]. Correspondingly, a recent scoping review on technology-based interventions for BPD shows that while evidence for Internet-based interventions is emerging, there is only little evidence for MHAs for BPD [ 12 ]. However, results on all five included MHAs supported their acceptance and/or usability [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, a recent scoping review on technology-based interventions for BPD shows that while evidence for Internet-based interventions is emerging, there is only little evidence for MHAs for BPD [ 12 ]. However, results on all five included MHAs supported their acceptance and/or usability [ 12 ]. A recent systematic review and meta-analysis on seven randomized controlled trials (RCTs) of MHAs for adults with common BPD symptoms [ 13 ] showed no significant effects between conditions with and without (e.g., waitlist, treatment-as-usual) MHAs on BPD-related symptoms.…”
Section: Introductionmentioning
confidence: 99%